XBRL Adoption Process in Malaysia Using Diffusion of Innovation Theory - ILIAS A.; GHANI E.K.; AZHAR Z. (Korea Distribution Science Association (KODISA), 2023)
The study examined the XBRL adoption process of Malaysian Business Reporting System (MBRS) by utilizing Everett Rogers Diffusion of Innovation (DOI) theory. The study focused on the three phases, namely, knowledge gathering and persuasion phase, decision-making phase, and implementation phase of XBRL adoption process gathered from a government agency in Malaysia. This study employs a qualitative case study that incorporates semi-structured interviews with four members of the regulator. The results reveal that the regulator has realized the advantages, management support, and need to skills development in phase one. On the other hand, in phase two, it finds the way the regulator makes decision related to XBRL taxonomy and submission template, platform, tools and software. Through phase three, the regulator is concerned with the complexity of XBRL taxonomy, resources, external support, promotion, stakeholder involvement, limited trading pressure, critical mass, and professional bodies. The factors from each phase suggest an in-depth understanding on the experience of XBRL through the development of MBRS that provides a success story to the other government agencies and regulators in Malaysia. This study provides several insights on the factors that could contribute to the adoption of XBRL and the Diffusion of Innovation theory adoption process. Copyright: The Author(s)